The Impact of Covid-19 on Consumption Patterns Among Malaysian Youths - Nursyuhada binti Jemey*; Nor Hasniah binti Kasim (The Institute of Academic Research and Publication (IARP), 2023)
This study investigates the impact of the COVID-19 pandemic on the consumption patterns of youth Malaysians, focusing on three important variables: changes in income, savings habits, and consumer credit. This study also aims to comprehensively understand the changing consumption patterns during the COVID-19 pandemic and the differences in consumption patterns between gender, living area, and educational level. As the primary method of data acquisition, 169 Malaysian youths aged 18 to 30 were administered a questionnaire. The findings revealed that changes in income, savings patterns, and consumer credit had a significant impact on the consumption patterns of Malaysian adolescents, thus concluding that the pandemic had a substantial impact on one’s financial behaviours. The results also revealed no significant difference in consumption patterns based on gender or residing area, but significant differences are obtained based on education level. Therefore, this study contributes to the existing body of knowledge regarding the effect of COVID-19 on consumption patterns and offers valuable guidance for various stakeholders in navigating the pandemic landscape.